2011
DOI: 10.1177/0960327111405865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead and/or cadmium on the distribution patterns of some essential trace elements in immature female rats

Abstract: Lead acetate (300 mg/L) and/or cadmium chloride (50 mg/L) were administered as drinking water to Sprague-Dawley rats for 9 weeks to investigate the effects of concurrent exposure to lead and cadmium on the distribution patterns of five essential trace elements. Inductively coupled plasma mass spectrometry was used to determine the concentrations of zinc, copper, manganese, selenium and iron in the urine at different exposure times, as well as their levels in the renal cortex and serum at the end of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…This effect of Mg could be explained by competitive antagonism between Cd and Mg at the level of GIT, as well as by corrective effect of Mg on Cd-induced extensive elimination of Zn via urine. Extensive loss of Zn via urine as a consequence of Cd exposure was previously confirmed not only in experimental conditions [25, 26], but also in workers exposed to Cd [27]. Moreover, a positive correlation between Cd and Zn in urine was found in individuals exposed to low levels of Cd in the environment [28].…”
Section: Discussionmentioning
confidence: 73%
“…This effect of Mg could be explained by competitive antagonism between Cd and Mg at the level of GIT, as well as by corrective effect of Mg on Cd-induced extensive elimination of Zn via urine. Extensive loss of Zn via urine as a consequence of Cd exposure was previously confirmed not only in experimental conditions [25, 26], but also in workers exposed to Cd [27]. Moreover, a positive correlation between Cd and Zn in urine was found in individuals exposed to low levels of Cd in the environment [28].…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, trace elements such as Cu and Zn can interact with the metabolism of Cd. Wang and colleges showed that exposure to Cd had resulted in a significant increase in the urinary excretion of Cu and Zn especially in kidney and serum (Wang et al, 2011). This study suggested that increasing urinary loss of antioxidant trace elements due to Cd exposure had induced the deficiency of antioxidants in the body, which could result in further oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Further oxidative damage to the rats exposed to high levels of Cd in drinking water could occur as a result of the increased urinary excretion of Se, Cu, Mn, and Zn, i.e. the elements involved in anti-oxidative processes (Wang et al 2011). More rarely, a potential synergistic effect of Se and other essential elements was assessed to enhance their protective effect against the Cdinduced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%